ESG and the mining industry: A Mongolian case study - Sternberg, T. (Journal of Environmental Assessment Policy and Management, 2025)
The principles of Environmental, Social and Governance (ESG) have an important role in the transition to clean energy technologies. ESG is vital to finance and investment in extractive industries that provide essential minerals. Yet mining presents significant landscape and livelihood challenges in affected communities. In fact, the industry considers ESG issues to be their greatest business risk. Research evaluates the role of ESG principles in Asian extractive industries, then focuses on the Mongolian context. In Mongolia, the $20 billion Oyu Tolgoi copper and gold mega-mine was investigated through extensive fieldwork at the site and in the local community. Research examined the mine’s environmental impact and socio-economic implications for residents. Results identified slow ESG uptake in the country and limited government engagement. From a herder perspective, over time, ESG principles enabled a local voice and a measure of accountability at the mine. It did not mitigate the severe impacts of mining in the community. While the government embraced international extractive agendas, strengthened ESG implementation and stronger monitoring are needed. For greater effectiveness mining communities should be involved in planning as early and open adherence to key principles would improve programme outcomes.